QUALITY COSTS : FACILITATING THE QUALITY INITIATIVE - Paulus Permatasari (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Ideas of what constitute quality costs have been changing rapidly. Whereas only a few years ago the costs of quality (COQ) were perceived as the cost of running the quality assurance department and the laboratory plus scrap and warranty costs, it is 'now widely accepted that they are the costs incurred in designing, implementing, operating, and maintaining quality management systems, the costs involved in introducing and sustaining a process of continuous and company — wide quality improvement, plus the costs incurred owing to failures of the systems, products and/or services. There is a general consensus that quality dollars expended on prevention and appraisal costs have the greatest return, and organizations spend the largest percentage of quality dollars in these categories. The remaining categories, failure costs (both internal and external), should ideally constitute only a minor percentage of total dollars spent on quality.The remaining category, failure costs (both internal and external), should ideally constitute only a minor percentage of total dollars spent on quality.Contrary to expectations, in many organizations, the highest percentage of the quality dollar is spent on the category with the lowest return, internal and external failures, followed by appraisal costs. Finally prevention costs, which produce the greatest return on investment, typically receive only a little share of the quality dollar.